DEVELOPMENT AND VALIDATION OF THE SELF-AWARENESS OF STRESS SCALE FOR TEACHERS - Mukhtar, Sonia; Farooq, Sadaf; Rafiq Dar, Muhammad (Journal of Pakistan Psychiatric Society, 2025)
OBJECTIVE To develop a reliable and valid self-report instrument assessing teachers’ self-awareness of stress. STUDY DESIGN Mixed-method research design PLACE & DURATION OF STUDY Three private and semi-government higher education institutions in Pakistan (Lahore and Multan), from September 2015 to September 2017 (for a duration of 02 years). METHOD To determine the psychometric properties of the Self-Awareness of Stress Scale (SSS), it was administered with a demographic proforma to a sample of 250 teachers. RESULTS Exploratory factor analysis, internal consistency, inter-factor correlations, and convergent validity were assessed. The Cronbach’s alpha coefficients ranged from 0.89 to 0.97, demonstrating excellent internal reliability. Inter-factor correlations and concurrent validities were statistically significant at p < 0.01. Three factors were extracted: Interpersonal Challenges, Personal Malfunctioning, and Work Inefficacy. CONCLUSION The SSS demonstrated strong reliability and validity, identifying three core domains, which were Interpersonal Difficulties, Personal Dysfunction, and Work Ineffectuality, that overall demonstrate teachers’ self-awareness of stress.